Evaluation d’activité anti-inflammatoire du Carthamus caeruleus L « Etude in vivo –chez les souris NMRI » - BOUHENNI, Ikram; BENKABLIA, Insaf (My University, 2019)
Many plants are known used in traditional medicine for the treatment of several diseases, including diseases with an inflammatory component similar to Carthamus caeruleus L. The purpose of this study was to evaluate the anti-inflammatory activity in vivo of aqueous extract of C.caeruleus streamer's roots by testing their toxicities at doses of 150 and 300mg /kg body weight, respectively, in oral administration modeled on the acute edema of the Caragenin induced mouse paw. these doses, the extracts exert no toxic effect, on the other hand, the study of the anti-inflammatory activity of the aqueous extract of the roots of C.caeruleus obtained by decoction at 10%, was determined in a mouse model of the inflammatory paw. An effective 20 mice was used, these mice are divided into four lots (five mice per batch). Each lot receives respectively, an oral solution of NaCl (control group), a solution of 50 mg / kg body weight Diclofenac (standard batch) and a solution of the aqueous extract of C. caeruleus (150 mg / kg of body weight and 300mg/kg). One hour later, all four lots were injected with 1% Carrageenan. Edema was assessed by measuring dorsal-plantar dorsal diameter (mm) before and after injection at intervals of 1%. One hour, for 6 hours. The study of the anti-inflammatory activity shows that the injection of Carrageenin causes a significant increase in the volume of the paw of the mice. Oral administration of Diclofenac (50mg/kg body weight) caused a decrease in mouse paw volume during the six hours of the experiment. In addition, at the first hour, the percentage inhibition of edema was (52.73%) in the group treated with the aqueous extract of C.caeruleus 150mg/kg body weight. This activity increases gradually until the sixth hour (95.4%). Similarly, similar results are reported a dose of 300 mg / kg body weight for the same plant. The histological study of diclofenac-treated sections and the aqueous extracts of C.caeruleus (150 and 300mg/kg of PC) shows the almost complete disappearance of the inflammatory infiltrate. These, confirm that these treatments have anti-inflammatory activity. All these results show that the aqueous extract of C.caeruleus exerts an anti-inflammatory effect. Because of this, it could be used as alternative compounds, particularly in the prevention against inflammation.
Keywords: Anti-inflammatory; Phytotherapy; C.caeruleus L; Carragenin; Diclofenac; in vivo.